(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Fibromyalgia is a disease characterized by chronic, widespread musculoskeletal pain, disturbed sleep, and problems with mental processing. For a long time, it was ignored by the medical community but now due to its increased prevalence, the situation has changed. Genetic and environmental factors like stress are related to its etiology. The present study aimed to assess the prevalence, and severity of fibromyalgia in medical students and the factors causing the disease. Methods: This study is a cross-sectional descriptive study conducted in Holy Family Hospital. Through convenience sampling methodology, 196 medical students of all five years of MBBS were included. The standard questionnaire, the Multidimensional Health Assessment Questionnaire (MDHAQ), was used. Students with trauma or inflammatory rheumatology diseases were excluded. Results: A total of 196 medical students were included of whom 54.6% (107/196) were females and 45.4% (89/196) were males. The total prevalence of fibromyalgia was calculated to be 68%, whereas 32% had no fibromyalgia or were in remission stage. The mean score for fibromyalgia calculated was 2.38 ± 1.81. There was a significant relationship between gender and having fibromyalgia (p = 0.000) with females (26.1%) suffering more from high severity fibromyalgia as compared to males (23.3%). Among our subjects with fibromyalgia symptoms, 72% reported that they did not exercise daily. Job or work status was found to significantly contribute to fibromyalgia (p = 0.003). Many functional and psychological problems were faced by people with fibromyalgia. Neck and back pain are the most significant. Conclusions: Fibromyalgia is alarmingly prevalent in medical students, affecting their social, functional, and daily lives. Patients with fibromyalgia suffer from a wide range of disorders, from psychological to severe physical pains, and the most important thing is that they frequently go undiagnosed. Medical students who face grinding education and training along with meagre psychological support are more prone to it. The issue at hand is worth the time and consideration of education policymakers.